A proposal of microtomography evaluation for restoration interface gaps - Deborah Meleo; Licia Manzon; Raffaella Pecci; Francesca Zuppante; Rossella Bedini
Nowadays, several adhesive systems are used in dental restoration and they're evaluated by clinical research. In vitro evaluations are often made by means of traditional observation techniques (for example scanning electron microscope (SEM), while 3D cone-beam microtomography technique (3D micro-CT), that can be able to generate 3D sample images without any sample treatment during acquisition data, is going to be used a lot in the next few years. In dental cavity restored with composite, it is possible to predict the presence of gaps due to polymerization shrinkage; that is the reason this work purpose is to reveal by 3D images and measure by micro-CT analysis the voids generated applying the most used adhesive systems at the moment. By means of microtomographic analysis is proposed an aid to overcome bidimensional SEM investigation limits like random observation of sample surface, sample sectioning (to see inside it with the relative possible structural alterations induced on the same sample) and the gold sputtering treatment. For this experimental work, human crown teeth have been selected, all restored with the same composite material, using five adhesive systems. After about 48 hours each tooth has been acquired by means of Skyscan 1072 micro-CT instrument and then processed by 3D reconstruction and micro-CT analyser software. Three adhesive systems have showed 3D micro-CT images with not as much voids as expected, with a very little extent. This kind of micro-CT in vitro evaluation proposal suggests a method to observe and quantify the voids generated after polymerization shrinkage during tooth restoration.